Use of calcium sulphate in alleviating salinity effects in tomato (Lycopersicon esculentum Mill.) - Ahmad, Nur Fatin (2018)
The fertigation system which uses soilless culture media is one of the efficient systems in cultivating variety of crops. However, the efficiency of this system is likely to be disrupted by abiotic stress such as salinity which contributed detrimental effects to plant growth and yield of crops. Hence, this study was conducted to evaluate the response of lowland tomato in the presence of medium and high concentration of salinity in terms of growth, physiology and yield, and to improve the yield and fruit quality using calcium as supplementation in the nutrient solution. Two tomatoes cultivars (Pearl and MT1) were grown under soilless culture system with basic nutrient solutions containing three different levels of NaCl (0, 70 and 140 mM) and observed at 4, 8 and 12 weeks after treatment. Significant effect of cultivars within NaCl treatment were shown by the plant height, total leaf area, shoot and root dry weight, and root to shoot ratio where they were all decreased as the NaCl level increased from week 4 until 12 after treatment. Cultivars within NaCl treatments showed significant effect on photosynthetic rate, stomatal conductance, total chlorophyll content and relative water content by showing the reduction from week 4 until 12 after treatment. The potassium and calcium concentration in both leaves and roots showed significant effect but decreased under saline condition, while sodium and chloride have a significantly high uptake due to the significant increase in electrolyte leakage. Salt stress had triggered the accumulation of proline in the leaves of the tomatoes, but not for lipid peroxidation. Salinity decreased total fruit yield to 83% for Pearl and 88% for MT1 at 140 mM NaCl. However, increasing NaCl concentration significantly increased total soluble solids, titratable acidity and blossom-end rot incidence. Tomato Pearl was more tolerant to salinity with higher fruit yield compared to MT1 at 70 mM NaCl. In order to improve tomato yield under saline condition, three concentrations of calcium sulphate (0, 2.5 and 10 mM) were added in the basic nutrient solution containing 70 mM NaCl. The addition of calcium significantly improved the growth of Pearl (plant height, total leaf area, shoot and root dry weight, shoot to root ratio) throughout the experiment. Photosynthetic rate, stomatal conductance, total chlorophyll content showed better activity at 2.5 mM CaSO4. The potassium and calcium concentration in the leaves of Pearl was well corrected after a supplementary of calcium by reducing the membrane permeability to Na+ and Cl-. Fruit yield, total soluble solids, titratable acidity, ascorbic acid, and blossom-end rot were significantly improved at 10 mM CaSO4. The supplementation of calcium was also effective in reducing the accumulation of proline and MDA content through improving the activity of antioxidant, phenolic and flavonoid content. In conclusion, application of calcium in the nutrient solution to alleviate salt stress effects is one of the simple practices that can be used in the soilless culture system which improves the growth, yield and quality of the fruits.